Design and Implementation of a Backstepping Time Varying Sliding Mode Control for the Angular Velocity Control of a Hydraulic Rotary Actuator - Abdullah, Aws M.; Al-Samarraie, Shibly A.; Ali, Hasan H.; Al-Qassar, Arif A. (Universitas Muhammadiyah Yogyakarta, 2025)
The Backstepping Sliding Mode Control is a control technique used for controlling nonlinear systems. In this paper, the performance of the backstepping sliding mode controller schemes for the angular velocity control for a rotary actuator of an angular velocity control system that utilizes a novel hydraulic flow control method called inlet throttling was investigated. For the angular velocity dynamic, a linear state feedback with suitable high gain is designed as the virtual controller, where steady state error can be made arbitrarily small according to the gain value. A time varying sliding variable is then selected based on the designed virtual controller. The resulting control design is robust, and the maximum error of the angular velocity with respect to the desired value is derived via Lyapunov Function where its value can be controlled via suitable selections of the control parameters. The simulation results have been obtained based on the MATLAB software tools, which are system transient response, the performance and the robustness of the proposed control in forcing the angular velocity to track the reference value in spite of the uncertainty and disturbances in the system parameters were studied. The SMC is a more comprehensive solution for ensuring the best robustness of stability and performance for the model. The simulation results were generated using MATLAB software tools., which are system transient response, the proposed control performance and the robustness in forcing the angular velocity to track the reference value (100-2000 RPM) in spite of the uncertainty (+10%) and disturbances (5-30 N.m) in the system parameters are studied.